Activisme culturel au Centre Georges-Pompidou. Le photoreportage exposé (1977-1997) - Assia Quesnel (Les Cahiers de l'École du Louvre)
During the final quarter of the twentieth century, photography progressively enjoyed cultural and artistic legitimisation in French institutions. Photo-reportage also profited from this process in order to respond to the protean crisis affecting its milieu. While it was not clear at first for a museum to include reportage photography, all of the departments of the Centre Pompidou sought to increase the status of the practice by making it part of the establishment’s cultural programming from 1977 to 1997, whatever the status imparted (document, work of art, cultural object). The Centre Pompidou thus appears as a place for the consecration of photo-reportage and the media. As for contemporary art, the institution was a place that activated photo-reportage especially in the decision to defend young artists, to show an interest in non-Western countries, and the commissioning of reportages.